A "Blockchain" Synergy in Conductive Polymer‐Filled Metal–Organic Frameworks for Dendrite‐Free Li Plating/Stripping with High Coulombic Efficiency. (27th January 2022) - Ma, Yong; Wei, Le; He, Ying; Yuan, Xuzhou; Su, Yanhui; Gu, Yuting; Li, Xinjian; Zhao, Xiaohui; Qin, Yongze; Mu, Qiaoqiao; Peng, Yang; Sun, Yang; et al.
Abstract: The performance of lithium‐metal batteries is severely hampered by uncontrollable dendrite growth and volume expansion on the metal anodes. Inspired by the "blockchain" concept in data mining, here we utilize a conductive polymer‐filled metal–organic framework (MOF) as the lithium host, in which polypyrrole (PPy) serves as the "chain" to interlink Li "blocks" stored in the MOF pores. While the N‐rich PPy guides fast Li + infiltration/extrusion and serves as the nucleation sites for isotropic Li growth, the MOF pores compartmentalize bulk Li deposition for 3D matrix Li storage, leading to low‐barrier and dendrite‐free Li plating/stripping with superb Coulombic efficiency. The as‐fabricated lithium‐metal anodes operate over 700 cycles at 5 mA cm −2 in symmetric cells, and 800 cycles at 1 C in full cells with a per‐cycle capacity loss of only 0.017 %. This work might open a new chapter for Li‐metal anode construction by introducing the concept of "blockchain" management of Li plating/stripping. Abstract : A novel concept of "blockchain" matrix Li storage is proposed by utilizing the N‐rich polypyrrole (PPy) as the "chain" to fill and interlink the "blocks" of MOF cavities. The lithiophilic PPy helps to guide fast infiltration/extrusion of Li + ions and serve as the nucleation sites for isotropic Li deposition, while the MOF pores enable the compartmentalization of the otherwise bulk Li deposition and provide spatial confinement for accommodating 3D matrix Li storage.